Molecular identification of the key starch branching enzyme-encoding gene SBE2.3 and its interacting transcription factors in banana fruits. (1st July 2020) - Miao, Hongxia; Sun, Peiguang; Liu, Qing; Liu, Juhua; Jia, Caihong; Zhao, Dongfang; Xu, Biyu; Jin, Zhiqiang
Abstract: Starch branching enzyme (SBE) has rarely been studied in common starchy banana fruits. For the first time, we report here the molecular characterization of seven SBE ( MaSBE ) and six SBE ( MbSBE ) genes in the banana A- and B-genomes, respectively, which could be classified into three distinct subfamilies according to genome-wide identification. Systematic transcriptomic analysis revealed that six MaSBE s and six MbSBE s were expressed in the developing banana fruits of two different genotypes, BaXi Jiao (BX, AAA) and Fen Jiao (FJ, AAB), among which MaSBE2.3 and MbSBE2.3 were highly expressed. Transient silencing of MaSBE2.3 expression in banana fruit discs led to a significant decrease in its transcription, which coincides with significant reductions in total starch and amylopectin contents compared to those of empty vector controls. The suggested functional role of MaSBE2.3 in banana fruit development was corroborated by its transient overexpression in banana fruit discs, which led to significant enhancements in total starch and amylopectin contents. A number of transcription factors, including three auxin response factors (ARF2/12/24) and two MYBs (MYB3/308), that interact with the MaSBE2.3 promoter were identified by yeast one-hybrid library assays. Among these ARFs and MYBs, MaARF2/MaMYB308 and MaARF12/MaARF24/MaMYB3 were demonstrated via a luciferase reporter system to upregulate and downregulate the expression of MaSBE2.3, respectively.